Memorisasi Kasih Allah Bagi Remaja Yatim Piatu Berdasarkan Teks Ulangan 6:4-9 di GMIT Polycarpus Atambua - Enos Januarinto Fina; Nelci Nafalia Ndolu; Catur Purnomo (Institut Agama Kristen negeri Kupang, 2021)
The orphaned teenager is in crisis about God's love for himself which affects his ability to love God as mandated in Deuteronomy 6: 4-5. Efforts are needed to base faith on orphaned youth by initiating the faith-based method in Deuteronomy 6: 6-9. The purpose of this study was to prove the possible effectiveness of applying the faith-based method in Deuteronomy 6: 4-9 to orphaned adolescents. The method used in this research is a combination research method, namely the simple qualitative and quantitative research methods. The results showed that the orphaned youth at GMIT Policarpus Atambua acknowledged that Allah is a God who loves, cares for and guides his life. However, this confession is obtained through a process of grounding faith in the form of repeated speech from family and church ministers such as pastors and Bible teachers; media symbols in family and PAR worship also strengthen the process of internalizing the concept of a God who is very loving